Evaluation of the Guiding Groove Technique in Periapical Endodontic Surgery: A Single-Blinded Randomized Controlled Trial - Jinghua Sun; Xiaolin Li; Chen Zhang; Benxiang Hou (Dental Hypotheses)
Introduction: We aimed to assess the clinical and radiographic outcomes following the use of the guiding groove technique in periapical endodontic surgery. Methods: Subjects with intact labial and buccal bone walls or defects with a maximum diameter of <3 mm, who met the inclusion criteria, were randomized into two groups using www.random.org. The experimental group (n = 15) underwent the “guiding groove” technique, while the control group (n = 15) underwent the traditional bone-removing fenestration. A total of 36 affected teeth were included. Follow-up visits were conducted at 1 week, and at 3, 6, and 12 months post-surgery, and efficacy was assessed through clinical and radiological examinations. Results: The success rate in the experimental group was 100%, while in the control group, it was 94.4% (P > 0.05). In the experimental group, 11.1% (2/18) of the teeth had a reverse preparation deviation angle of >15°, and 44.4% (8/18) in the control group (P = 0.016). Conclusion: The modified osteopathic fenestration method of “guiding groove” is safe and feasible, preserving more labiobuccal cortical plate for the affected tooth and effectively reducing the surgical trauma of patients.